Fluvoxamine maleate alleviates amyloid-beta load and neuroinflammation in 5XFAD mice to ameliorate Alzheimer disease pathology - Kaur, Sukhleen; Sharma, Kuhu; Sharma, Ankita; Sandha, Kamalpreet Kaur; Ali, Syed Mudassir; Ahmed, Riyaz; Ramajayan, P.; Singh, Parvinder Pal; Ahmed, Zabeer; Kumar, Ajay (Frontiers in Immunology, 2024)
Alzheimer pathology (AD) is accompanied by the deposition of amyloid beta (Aβ) and chronic neuroinflammation. We found that the OCD drug fluvoxamine maleate (FXN) can potently ameliorate AD pathology in 5XFAD mice by autophagy-mediated clearance of Aβ and inhibition of NLRP3 inflammasome. Our data showed that FXN induces autophagy to inhibit NF-κB and NLRP3 inflammasome at 78 nM apart from directly inhibiting NLRP3 inflammasome in primary astrocytes. FXN activated the PRKAA2 pathway through CAMKK2 signaling, leading to the induction of autophagy in primary astrocytes. FXN inhibited the ATP-mediated activation of NLRP3 inflammasome through autophagic degradation of NF-κB and thus caused the downregulation of pro-IL-1β and NLRP3. The anti-NLRP3 inflammasome effect of FXN was reversed when autophagy was inhibited by genetic knockdown of the PRKAA2 pathway or bafilomycin A1. Furthermore, FXN treatment improved AD pathology in 5XFAD mice, which significantly improved multiple behavior parameters like working memory and neuromuscular coordination; more importantly, they behaved more like wild-type animals. We found that FXN improved behavior in 5XFAD mice by clearing the Aβ deposits from the hippocampi along with a significant reduction in multiple inflammatory proteins, including NF-κB, GFAP, IBA1, IL-1β, TNF-α, and IL-6 associated with NF-κB and NLRP3 inflammasome in the brain. Moreover, these changes were accompanied by increased expression of autophagic proteins. Our data suggest that to ameliorate AD pathology, FXN simultaneously targets two key pathological features of AD: Aβ deposits and neuroinflammation. Being an approved drug, FXN can be pushed as a potential drug candidate for human studies against AD.